Fiscal Buffers for Natural Disasters in Pacific Island Countries - Nishizawa, Hidetaka; Roger, Scott; Zhang, Huan. (Washington, D.C. : International Monetary Fund, 2019)
Pacific island countries (PICs) are vulnerable severe natural disasters, especially cyclones, inflicting large losses on their economies. In the aftermath of disasters, PIC governments face revenue losses and spending pressures to address post-disaster relief and recovery efforts. This paper estimates the effects of severe natural disasters on fiscal revenues and expenditure in PICs. These are combined with information on the frequency of large disasters to calculate the rate of budgetary savings needed to build appropriate fiscal buffers. Fiscal buffers provide self-insurance against natural disaster shocks and facilitate quick disbursement for recovery and relief efforts, and protection of spending on essential services and infrastructure. The estimates can provide a benchmark for policymakers, and should be adjusted to take into account other sources of financing, as well as budget risks from less severe as well as more frequent disasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet